Antinociceptive Effect of Intrathecal Injection of Genetically Engineered Human Bone Marrow Stem Cells Expressing the Human Proenkephalin Gene in a Rat Model of Bone Cancer Pain - Yi Sun; Yuke Tian; Haifeng Li; Dengwen Zhang; Qiang Sun (Pain Research and Management)
Background. This study aimed to investigate the use of human bone marrow mesenchymal stem cells (hBMSCs) genetically engineered with the human proenkephalin (hPPE) gene to treat bone cancer pain (BCP) in a rat model. Methods. Primary cultured hBMSCs were passaged and modified with hPPE, and the cell suspensions (6 × 106) were then intrathecally injected into a rat model of BCP. Paw mechanical withdrawal threshold (PMWT) was measured before and after BCP. The effects of hPPE gene transfer on hBMSC bioactivity were analyzed in vitro and in vivo. Results. No changes were observed in the surface phenotypes and differentiation of hBMSCs after gene transfer. The hPPE-hBMSC group showed improved PMWT values on the ipsilateral side of rats with BCP from day 12 postoperatively, and the analgesic effect was reversed by naloxone. The levels of proinflammatory cytokines such as IL-1β and IL-6 were ameliorated, and leucine-enkephalin (L-EK) secretion was augmented, in the hPPE-engineered hBMSC group. Conclusion. The intrathecal administration of BMSCs modified with the hPPE gene can effectively relieve pain caused by bone cancer in rats and might be a potentially therapeutic tool for cancer-related pain in humans.